Role of dietary fish oil and plant oil supplements in ruminal lipid metabolism and fish oil induced milk fat depression in lactating cows : Doctoral Dissertation - Kairenius, Piia (Natural Resources Institute Finland, 2020)
The objective of the research described in this thesis was to provide new information on the ruminal biohydrogenation of long-chain n-3 polyunsaturated fatty acids (PUFA), such as 20:5n-3, 22:5n-3 and 22:6n-3, for altering bovine milk fatty acid (FA) composition, with the potential to improve human health. Emphasis was not only placed on the potential to increase milk fat n-3, but also to modulate ruminal lipid metabolism and to explore the mechanisms driving milk fat synthesis and its regulation in lactating cows in order to understand the mechanisms and metabolic pathways underlying the diet-induced changes in milk fat depression (MFD), milk FA composition and specific FA intermediates and end products associated with MFD. Experiments documented in I–IV encompassed detailed investigations of ruminal (I-III) and mammary (IV) lipid metabolism. Experiment reported in I was conducted to build up methods for the analysis of long-chain 20- to 22-carbon FA intermediates formed during ruminal biohydrogenation of n-3 PUFA. The detailed analysis of fish oil (FO) and omasal digesta of lactating cows fed FO enabled the structure identification of 27 previously unidentified 20- to 22-carbon FA intermediates, containing at least one trans double bond. No conjugated 20-carbon FA were detected in omasal digesta. Results demonstrated that the hydrogenation of 20:5n-3, 22:5n-3 and 22:6n-3 in the rumen proceeds via two principal mechanisms that involve sequential reduction or isomerisation of cis double bonds closest to carboxyl group and provided clear evidence of extensive biohydrogenation of 20:5n-3, 22:5n-3 and 22:6n-3 in cows fed FO. Experiments documented in II-IV involved two physiological studies in which, the effects of dietary FO supplements alone (II; IV) or in combination (III) with sunflower (rich in 18:2-6; SFO) or linseed (rich in 18:3n-3; LFO) oil on animal performance (II-IV), ruminal lipid metabolism (II; III), microbial ecology in the rumen (II; III) and milk fat composition (IV) were investigated in lactating cows. Dietary FO supplements increased the intakes of 20:5n-3, 22:5n-3, 22:6n-3 and total FA (II; III), whereas decreased dry matter intake (II; III). Dietary oil supplements decreased (II) or had no effect (III) on ruminal volatile FA concentrations, but FO at high amounts (II) or when supplemented with plant oils (III) promoted an increase in molar proportions of propionate (II; III) and butyrate (II) at the expense of acetate (II; III). Supplements of FO modified ruminal metabolism of 16- and 18-carbon PUFA, causing increases in trans 16:1, trans 18:1 and trans 18:2 flow and a decrease in 18:0 at the omasum, and at high amounts promoted trans-10 18:1 accumulation at the expense of trans-11 18:1. Dietary FO had no substantial influence on ruminal outflow of conjugated linoleic acid (CLA). Extensive ruminal biohydrogenation of 20:5n-3, 22:5n-3 and 22:6n-3 resulted in increases in numerous 20- and 22-carbon PUFA containing at least one trans double bond at the omasum. Relative to FO, ruminal metabolism of 22:6n-3 was more extensive on diets containing plant oils, whereas the biohydrogenation of 22:5n-3 and 20:5n-3 showed no difference between FO and diets containing plant oils (III). The inhibitory effects of FO on the reduction of 18-carbon PUFA to 18:0 were influenced by the source of 18-carbon PUFA in SFO and LFO. The ruminal outflow of 18:0 was lower and accumulation of trans 18:2 and 20- to 22-carbon FA intermediates greater for LFO than SFO. Supplements of SFO and LFO caused trans-10 and trans-11 18:1 to accumulate, trans-10 18:1 being the most abundant FA intermediate in SFO. Alterations in the ruminal metabolism of FA were not associated with substantial changes in rumen protozoal counts or analysed bacterial populations known to be capable of biohydrogenation (II; III), but lowered Butyrivibrio spp. numbers in response to increasing levels of FO (II). Supplements of FO decreased milk fat yield and content and increased 20:5n-3, 22:5n-3 and 22:6n-3 concentrations in milk fat (IV). Enrichment of milk long-chain n-3 PUFA was associated with decreases in 4- to 18-carbon saturated FA and several-fold increases in CLA, trans FA and PUFA concentrations. Dietary FO resulted in the appearance of 37 unique 20- and 22-carbon FA in milk. FO-induced MFD (up to -40.6 % reduction in milk fat synthesis) was associated with changes in the concentrations of multiple FA in milk, in particular increases in milk fat trans-10 18:1 and cis-11 18:1 concentrations, but not with changes in the amount of trans-10,cis-12 CLA in milk and omasum or estimated milk fat melting point (IV). The negative relationship between ruminal outflow of trans-10 18:1 and milk fat secretion confirmed that a shift in ruminal biohydrogenation of 18-carbon FA toward trans-10 pathway has a role in the regulation of milk fat synthesis during FO-induced MFD. A decrease in 18:0 supply in combination with increased mammary uptake of cis-11 18:1, trans-10 18:1, and trans 20- and 22-carbon FA intermediates originating from the rumen may contribute to the reduction of milk fat observed during FO-induced MFD. The dietary supplements of FO alone or in combination with plant oils increased the ruminal outflow of FA intermediates containing at least one trans double bond and enriched long-chain n-3 PUFA in bovine milk with associated changes in the abundance and distribution of FA. These changes may have implications for the host metabolism and the nutritional quality or ruminant-derived foods.
Keywords: biohydrogenation; rumen; fish oils; plant oil; sunflower oil; linseed oil; lactating cow; polyunsaturated fatty acid; n-3 fatty acid; conjugated linoleic acid; milk fat; trans fatty acid; Butyrivibrio; microbial ecology; gas chromatography; mass spectrometry; silver-ion thin-layer chromatography